PENGARUH TERAPI SEFT (SPIRITUAL EMITIONAL FREEDOM TECHNIQUE) TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI DI UPT PUSKESMAS MEDAN TUNTUNGAN - Fridella Grace Natalia Tarigan, Yosafat Barus, Tetty Suriany Limbong (JURNAL PIONIR, 2022)
AbstractBackground: Spiritual emotional freedom technique (SEFT) therapy is a therapy in the form of a combination of the energy system (energy medicine) and Spiritual therapy combined with tapping at predetermined points on several body parts which is almost the same as acupuncture and acupressure techniques by stimulating several key points along the body's 12 energy meridians. Objective: To determine the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on reducing blood pressure in hypertensive patients in the UPT Puskesmas Medan Tuntungan Work Area. Methods: This research uses a pre-experimental approach using the One Group pretest-posttest approach. The population in this study were hypertensive patients at UPT. Tuntungan Health Center as many as 2,792 population. Sampling is an accidental sampling technique with a sample of 15 respondents. The instrument used is an observation sheet, while the test is the Wilcoxon test. Results: systolic blood pressure before the intervention was given an average of 170.00 mmHg and diastolic blood pressure an average of 91.33 mmHg. Meanwhile, after the intervention, the average systolic blood pressure was 142.67 mmHg and the average diatolic blood pressure was 78.00 mmHg. Conclusion: There is an effect of Spiritual Emotional Freedom Technique (SEFT) therapy on reducing blood pressure of hypertensive patients in the Work Area of UPT Puskesmas Medan TuntunganKeywords: Spiritual Emotional Freedom Technique (SEFT), blood pressure Abstrak Latar Belakang: Terapi spiritual emotional freedom technique (SEFT) adalah suatu terapi yang berupa gabungan dari sistem energy pada (energy medicine) dan terapi Spritual gabungan tapping pada titik yang sudah tentukan pada beberapa bagian tubuh yang hampir sama dengan tehnik akupuntur dan akupresur dengan merangsang beberapa titik titik kunci pada sepanjang 12 jalur energi (energy meridian) tubuh. Tujuan: Untuk mengetahui Pengaruh terapi Spiritual Emotional Freedom Technique (SEFT) terhadap penurunan tekanan darah pasien hipertensi di Wilayah Kerja UPT Puskesmas Medan Tuntungan. Metode: Penilitian menggunakan pre eksperimental yang menggunakan pendekatan One Group pretest-posttest. Populasi dalam penelitian ini adalah penderita hipertensi di UPT. Puskesmas Tuntungan sebanyak 2.792 populasi. Pengambilan sampel adalah teknik accidental sampling dengan jumlah sampel 15 responden. Instrumen yang digunakan adalah lembaran observasi sedangakan pengujiaan dengan uji wilcoxon. Hasil: Tekanan darah sistolik sebelum diberikan intervensi rata – rata 170,00 mmHg dan tekanan darah diastolik rata – rata 91,33 mmHg. Sedangkan sesudah dilakukan intervensi didapatkan tekanan darah sistolik rata – rata 142,67 mmHg dan tekanan darah diatolik rata – rata 78,00 mmHg. Kesimpulan: Ada pengaruh Terapi Spiritual Emotional Freedom Technique (SEFT) terhadap penurunan tekanan darah pasien hipertensi di Wilayah Kerja UPT Puskesmas Medan Tuntungan.